Effective Heterogeneous Fenton‐Like degradation of Malachite Green Dye Using the Core‐Shell Fe3O4@SiO2 Nano‐Catalyst. Issue 4 (26th January 2021) - Mahmud, Nafis; Benamor, Abdelbaki; Nasser, Mustafa S.; Ba‐Abbad, Muneer M.; El‐Naas, Muftah H.; Mohammad, Abdul Wahab
Abstract: In this study, the application of the core‐shell Fe3 O4 @SiO2 nano‐catalysts for fenton‐like degradation of malachite green dye has been presented. The nano‐catalysts were prepared using a combination of solvothermal and sol‐gel techniques and characterized using XRD, FTIR, SEM/EDX, TEM and VSM techniques. The effects of various reaction parameters on the degradation of malachite green dye using the prepared nano‐catalysts were investigated. The optimal condition for pH, catalyst dosage and H2 O2 amount were found to be at 6.7, 15 mg and 50 μL, respectively. Under the optimized conditions, a degradation efficiency of 96.18 % for malachite green dye was achieved using the catalyst within 30 minutes at 303 K with a pseudo first order rate constant of 0.1102 min −1 . The plausible mechanism for MG degradation was determined to be the combination of adsorption and simultaneous decomposition via formation of hydroxyl radicals. The performance of the nano‐catalyst was compared with other fenton‐like catalysts reported in the literature. Finally, the magnetic properties of the Fe3 O4 @SiO2 catalysts was utilized for its successful recovery and application in multiple degradation cycles. Abstract : Fe3 O4 @SiO2 nanoparticles were synthesized using combined solvothermal and sol‐gel approach and characterized using various techniques. The synthesized nanoparticles were then applied for fenton‐like degradation of malachite green dye. The effect of various reaction parameters like pH, catalyst dosage and H2 O2 amount were investigated and the optimum conditions for dye degradation were determined. A kinetics study conducted under optimized conditions revealed that the synthesized Fe3 O4 @SiO2 nanoparticles were highly effective for Malachite green dye degradation with good recyclability.